2002
DOI: 10.1086/341922
|View full text |Cite
|
Sign up to set email alerts
|

Matrix‐Assisted Laser Desorption/Ionization Time‐of‐Flight Mass Spectrometry and Proteomics: A New Era in Anaerobic Microbiology

Abstract: Genome sequence data provide a framework for predicting potential microbial activities; however, the proteome content of the cell dictates its response to its environment. Microbiology is witnessing a major initiative to elucidate the nature of the proteome of large numbers of species. The tool driving the proteomic revolution is matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. During the analysis process, proteins are ionized and separated on the basis of their mass-to-charge rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 19 publications
(11 reference statements)
0
25
0
Order By: Relevance
“…MALDI-TOF MS has also been utilized to evaluate subsets of anaerobic microorganisms isolated from defined biological niches. The applicability of this method for routine identification of important human-pathogenic anaerobic bacteria was evaluated by Shah et al, who showed that through the use of intact-cell MALDI-TOF MS, Porphyromonas strains could be differentiated (243). Nagy et al reported 97% accuracy at the species level for 277 isolates and 9 species of Bacteroides (244).…”
Section: Anaerobic Bacteriamentioning
confidence: 99%
“…MALDI-TOF MS has also been utilized to evaluate subsets of anaerobic microorganisms isolated from defined biological niches. The applicability of this method for routine identification of important human-pathogenic anaerobic bacteria was evaluated by Shah et al, who showed that through the use of intact-cell MALDI-TOF MS, Porphyromonas strains could be differentiated (243). Nagy et al reported 97% accuracy at the species level for 277 isolates and 9 species of Bacteroides (244).…”
Section: Anaerobic Bacteriamentioning
confidence: 99%
“…A retrospective study by Eigner et al (2009) on more than 1000 routine isolates representing the main bacterial groups encountered in a clinical microbiology laboratory showed 95.2 % correct identification by MALDI-TOF MS, whereas Seng et al (2009) showed that out of 1660 clinical isolates representing 109 different species, they could identify correctly only 84.1 % at the species level. Shah et al (2002) predicted that MALDI-TOF MS would bring a new era in anaerobic microbiology. Several studies have been carried out since then, and the results of different reports demonstrate that superior identification of anaerobic bacteria can be achieved using MALDI-TOF MS for anaerobic isolates in routine laboratories (Justesen et al, 2011;La Scola et al, 2011;Veloo et al, 2011;Wybo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These papers mainly describe the use of the ProteinChip Arrays with purified proteins [10][11][12][13][14], or extracted surface proteins [15][16][17][18][19]. A few reports are available in the literature in which this technology is used with protein extracts [20][21][22]. We are primarily interested in the study of Streptococcus pneumoniae and its response to antibiotic treatments.…”
mentioning
confidence: 99%
“…Even in the microbiology field, under certain conditions, only limited sample quantities are available (this work, [22]). A technology like SELDI-TOF, with adequate sensitivity to generate data from minimal starting material, is very valuable in such cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation